Molecular anchoring of free solvents for high-voltage and high-safety lithium metal batteries - Cui, Zhuangzhuang; Jia, Zhuangzhuang; Ruan, Digen; Nian, Qingshun; Fan, Jiajia; Chen, Shunqiang; He, Zixu; Wang, Dazhuang; Jiang, Jinyu; Ma, Jun; Ou, Xing; Jiao, Shuhong; et al. (Nature communications, 2024)
Constraining the electrochemical reactivity of free solvent molecules is pivotal for developing high-voltage lithium metal batteries, especially for ether solvents with high Li metal compatibility but low oxidation stability ( <4.0 V vs Li + /Li). The typical high concentration electrolyte approach relies on nearly saturated Li + coordination to ether molecules, which is confronted with severe side reactions under high voltages ( >4.4 V) and extensive exothermic reactions between Li metal and reactive anions. Herein, we propose a molecular anchoring approach to restrict the interfacial reactivity of free ether solvents in diluted electrolytes. The hydrogen-bonding interactions from the anchoring solvent effectively suppress excessive ether side reactions and enhances the stability of nickel rich cathodes at 4.7 V, despite the extremely low Li + /ether molar ratio (1:9) and the absence of typical anion-derived interphase. Furthermore, the exothermic processes under thermal abuse conditions are mitigated due to the reduced reactivity of anions, which effectively postpones the battery thermal runaway. Advanced electrolyte is essential for high-energy-density lithium metal batteries. Here, the authors design a molecular anchoring dilute electrolyte via intermolecular hydrogen bonding with free solvents to improve the battery electrochemical and thermal stabilities.